Flight control systems practical issues in design and implementation - Pratt, Roger 1943- (Institution of Engineering and Technology American Institute of Aeronautics and Astronautics, 2000)
The book aims to build on the fundamentals of flight dynamics and flight control and embellish these principles by assigning their relevance to the development of flight control systems in the aircraft industry. The book comprises 9 chapters and deals with the following subjects: industrial considerations for flight control; aircraft modelling; actuation systems; handling qualities; automatic flight control system design considerations; ground and flight testing of digital flight control systems; aeroservoelasticity; eigenstructure assignment applied to the design of an autopilot function for a civil aircraft; and Hinfinity loop-shaping design for the VAAC Harrier.